THE USE OF PICTIONARY GAMES IN IMPROVING STUDENTS’ VOCABULARY MASTERY IN SMPN 8 SATAP TONDANO - Gloria Anastasia Suoth; Mister Gidion Maru; Rinny Rorimpandey (SoCul: International Journal of Research in Social Cultural Issues, 2021)
This research was proved whether the use of Pictionary games in teaching vocabulary can improve students’ vocabulary mastery or not. This research used the quantitative method with the pre-experimental design, one group pre-test and post-test design. Pre-test (T1) is given to the students before treatment and post-test (T2) is given after treatment. This research was conducted SMP Negeri 8 Satap Tondano especially 7th grade students. There were three classes of the first level students, and the researcher will take one class only and it will be chosen as the subject of study with the total number of participants 23 students. Based on the findings, it could be concluded that the use of Pictionary as the learning method to improve students’ vocabulary mastery is an effective way to solve students’ lack in vocabulary mastery, especially the understanding of the meaning of each English word. The result showed the score in the post-test is significantly higher than pre-test. Most of the students found the effectiveness of this method in their English learning activity such as reading, speaking, and listening. The following suggestions are regarded as important to be considered by English teachers concerning the way of teaching vocabulary: 1) English teachers at junior high school are suggested to apply Pictionary games to help the students in learning vocabulary. 2) The teachers must control the students in groups to make them active and initiative. 3) Teachers must be creative to find out teaching technique that could improve students’ mastery in Vocabulary.